(untitled) (Saúde & Tecnologia, 2025)
Introduction – Urinary incontinence (UI) or involuntary loss of urine is a frequent and concerning health condition, which can be subdivided into three common types: stress, urge, or mixed UI. Objectives – To identify the prevalence of UI in women in the municipality of Seia and evaluate the impact of UI on quality of life (QoL). Methods – A descriptive observational study with analytical characteristics was conducted, using a convenience sample of women in the municipality of Seia (n=416), with a subsample of incontinent women (n=117). A sample characterization questionnaire and the Contilife® measurement instrument were used. Inferential analysis was performed using the Chi-Square test, Student’s t-test, and Likelihood Ratio (LR) measure. Internal consistency was assessed using Cronbach’s Alpha. Results – The prevalence for the population of Seia was 28.1%, with a significant association between parity and the presence of UI, with a large LR value. UI has an impact on women’s QoL (59%), as measured by Contilife® (mean 7.59 in overall QoL), with mixed UI causing the most pronounced effect (73.3%). Conclusion – Female UI impacts on QoL with statistically significant values in all Contilife® dimensions, although classified as low impact. Physiotherapists can be first-contact professionals, allowing the quantification of women with UI and acting in the prevention and treatment of this condition, leading to physiotherapy being a guideline for improving quality of life.